Approximation to the concepto of protected interest in a "colonized criminal law" :colombian case (2010)
This paper presents some details on the concept of juridical protected interest originated in the tradition of civil law, in an example of colonized criminal law: the Colombian case. This paper deals with an approach to the study of the arrival of this co